Deakin University: Going Online At A Dual Mode University - Calvert, Jocelyn (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2001)
Deakin is a dual mode university with more than half of its students doing at least part of their study at a distance and with an entrepreneurial arm that provides distance education services for even larger numbers. Online provision has been developing over a decade, enriching traditional distance education in programs with mixtures of on- and off-campus students. It has been supported by central services and corporate applications, leading to reasonable consistency in the thrust. A current aim is to ensure that it is sustainable at a high level of quality.